Trophoblast cell-surface antigen 2 (TROP2) expression in triple-negative breast cancer - Yeonjin Jeon; Uiree Jo; Jongmoo Hong; Gyungyub Gong; Hee Jin Lee (BMC Cancer, 2022)
Abstract Background Trophoblast cell-surface antigen 2 (TROP2) is related to tumor proliferation enhancement and poor prognosis. An antibody targeting TROP2 was developed to treat metastatic triple-negative breast cancer (TNBC) which has a limited treatment modality. To characterize the TROP2 expressing tumors in TNBC, we analyzed TROP2 expression in three cohorts; (1) primary tumor without neoadjuvant chemotherapy, (2) primary tumor with neoadjuvant chemotherapy, and (3) metastatic tumor. Methods A total of 807 TNBC cases were evaluated for TROP2 immunohistochemical expression. We evaluated the TROP2 H-score distribution in the three cohorts. Tumors were divided into two groups based on TROP2 expression (high vs. low). We analyzed the relationship between clinicopathologic features and markers, including epidermal growth factor receptor, cytokeratin 5/6, p53, and Ki-67, and prognostic significance at high vs. low TROP2 expression. Results There was no difference in TROP2 H-score distribution between the three cohorts. Moderate-to-strong membranous expression of TROP2 in at least 10% of tumor cells was present in 662 cases (82.0%) in Cohort 1, 59 cases (89.4%) in Cohort 2, and 23 cases (88.5%) in Cohort 3. There was no significant difference in clinicopathologic features between high vs. low TROP2 in all cohorts. TROP2 H-score was an independent poor prognostic factor for overall survival in Cohort 3. Conclusions TNBC showed similar TROP2 expression regardless of neoadjuvant treatment or primary tumor/metastasis. Although the prognostic significance of TROP2 expression in metastatic TNBC has been revealed, further evaluation of the predictive value of TROP2 expression for targeted therapy is needed.